Microbial soil quality indicators depending on land use and soil type in a semi-arid dryland in Kenya - Mganga, Kevin Z.; Rolando, José; Kalu, Subin; Karhu, Kristiina (European journal of soil biology, 2024)
Soil microbial indicators help monitor soil quality. Limited studies have determined how land use in drylands affects soil microbial indices. Top soil (0–10 cm) from four land use systems in African drylands: (1) shrubland (natural), (2) grassland (natural), (3) pasture (agricultural) and (4) cropland (agricultural) occurring on two soil types: (1) Vertisol and (2) Acrisol, was used in laboratory incubations (6 days) to assess the effects of land use changes on organic carbon (Corg) mineralization, microbial biomass C (Cmic), mineralization quotient (qM), metabolic quotient (qCO2), Cmic:Corg ratio and sensitivity indices of these microbial indicators. Experimental plots were organized into a completely randomized design (n = 3) for every combination of land use and soil type. Cumulative CO2 produced from native Corg mineralization was the highest in Acrisol (108 ± 2.7 μg CO2–C g−1 soil) and the lowest in Vertisol (53 ± 2.5 μg CO2–C g−1 soil) croplands. Vertisol shrubland (1.34 ± 0.09 mg C g−1 soil) and Acrisol cropland (0.28 ± 0.07 mg C g−1 soil) had the highest and the lowest Cmic, respectively. Acrisol cropland (1.29 μg CO2–C g−1 h−1) had the highest qM, approximately five times higher than the lowest qM (0.26 μg CO2–C g−1 h−1) in a Vertisol cropland. Highest qCO2 was observed in an Acrisol pasture (12.04 μg CO2–C g−1 Cmic h−1), which was approximately 30 times higher compared to the lowest qCO2 observed in a Vertisol shrubland (0.41 μg CO2–C g−1 Cmic h−1). The Cmic:Corg ratio was the highest in a Vertisol shrubland (0.097), approximately five times higher than the lowest observed in an Acrisol pastureland (0.019). Our study demonstrated that the measured soil quality indicators' magnitude, direction, and sensitivity varied depending on land use and soil type. Higher N availability in Vertisols increased the biological stability of soil organic carbon (SOC) resulting to decreased SOC mineralization than Acrisols. In conclusion, the measured microbial soil quality indicators showed that Acrisols are prone to accelerated SOC mineralization after disturbance than Vertisols in the studied semi-arid dryland ecosystems. Thus, there is a need to manage natural ecosystem conversions to support sustainable crop and pasture production in African drylands. [Display omitted]